Investigating Fungi-Derived Bioactive Molecules as Inhibitor of the SARS Coronavirus Papain Like Protease: Computational Based Study - Belachew, Aweke Mulu; Feyisa, Asheber; Mohamed, Seid Belay; W/Mariam, Jerusalem Fekadu (Frontiers in Medicine, 2021)
Recently, due to rapid growth of the COVID-19 pandemic across the world, therapeutic development to fight the novel severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) is critical. Up to know it has been infected more than seventeen million and killed more than half a million people according to 1 August 2020 WHO report. Different type of studies has been conducted to develop anti-viral drug for COVID-19 with no success yet. But, developing new antiviral drug is laborious, expensive and time-consuming by using wet lab approach. Thus, one of the best alternatives to tackle this virus at present is to screen bioactive compounds by using computational approaches. As part of this, silico studies used to discover and introduce COVID-19 antiviral drugs and results showed that protease inhibitors can be very effective in controlling virus-induced infection. At the time of pathogenesis, Papain-like protease (PLpro) is responsible for processing the translated polyprotein chain from the viral RNA yielding functional viral proteins. This study proposed to screen fifty (50) Pub-Chem retrieved fungi derived bioactive compounds against SARS-CoV-2 Papain-like protease (PLpro) by using Auto Dock 4.2.1, Gromacs 2018.2, ADMET, SwissADME, FAF-Drugs 4.023, pKCSM and UCLA-DOE server. Among screened bioactive compounds Dihydroaltersolanol C, Anthraquinone, Nigbeauvin A, and Catechin were selected with Auto-Dock results -8.68, -7.52, -10.46, and -10.58 Kcal/mol, respectively. They interact with amino acids residues Gly163, Trp106, Ser111, Asp164, and Cys270 through hydrogen bonds. And then, subjected to Molecular dynamics simulation and result revealed that RMSD, RMSF, SASA and Rg value is in a good compatibility with docking results. In General, in this study Fungi derived bioactive compounds used as PLpro inhibitor pave the way for rapid in-vitro and in-vivo studies to battle the SARS-CoV-2.